Masa Depan Indonesia yang Mencemaskan Perspektif Sosiologis - Sobirin Malian (Unisia, 2003)
The condition of our society today seems to be overwheimed by sociai turbuience, the randomness and irreguia*, the absurd political discourse, radical fluctuation of economic sectors, never ending social violence, and uncertainty of cultural values. The suggestions made by the writer are: first, the symbols shift, means the politic of information system must aimed to create productivity and creativity for further society development. Second, normative reformation, means, transparency of court system, legal certainty, and excludes the legal procedure away from political interest.